1997
DOI: 10.1001/archinte.157.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depression in elderly primary care patients. A comparison of the Center for Epidemiologic Studies-Depression Scale and the Geriatric Depression Scale

Abstract: The CES-D and the GDS have excellent properties for use as screening instruments for major depression in older primary care patients. Because the GDS's yes or no format may ease administration, primary care clinicians should consider its routine use in their practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
337
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(353 citation statements)
references
References 0 publications
7
337
0
9
Order By: Relevance
“…While the highest possible sensitivity and specificity are preferable, these values are impressive for a brief seven-item instrument evaluating multiple dimensions of distress with a specificity similar to that of other commonly used instruments designed to screen for only a single dimension of distress. [24][25][26][27][28][29][30][31] The exact PWBI score (0-7) is even more useful at the individual level, where the post-test probability of an individual physician having low mental QOL can be reduced to < 1 % or raised to > 75 %.…”
Section: Discussionmentioning
confidence: 99%
“…While the highest possible sensitivity and specificity are preferable, these values are impressive for a brief seven-item instrument evaluating multiple dimensions of distress with a specificity similar to that of other commonly used instruments designed to screen for only a single dimension of distress. [24][25][26][27][28][29][30][31] The exact PWBI score (0-7) is even more useful at the individual level, where the post-test probability of an individual physician having low mental QOL can be reduced to < 1 % or raised to > 75 %.…”
Section: Discussionmentioning
confidence: 99%
“…Instruments commonly used to collect data on utilities include the EuroQol-EQ-5D (Brooks 1996;Langelaan et al 2007;van Hout et al 2012;Butt et al 2013), the SF-6D (Espallargues et al 2005;Butt et al 2013), the Geriatric Depression Scale (Lyness et al 1997) and other rating scale questionnaires. Health utilities typically are estimated from time trade-off (Weinstein et al 2009) or standard gamble methods (Drummond et al 1987), or from one of several stated-preference methods (e.g., discrete choice (Kessels et al 2011), pairwise comparison (Bradley & Terry 1952), best-worst scaling (Flynn et al 2007), or iterative bidding games (Brookshire & Crocker) ).…”
Section: Precismentioning
confidence: 99%
“…The psychometric properties reported here therefore need to be verified when the scales are administered independently. In addition, the effectiveness that these short forms of the GDS (van Marwijk et al, 1993;D'Ath et al, 1994;Lyness et al, 1997;Arthur et al, 1999;Molloy et al, 2006) have shown in screening for depression …”
Section: Geriatric Depression Scale In Palliative Carementioning
confidence: 99%